2019
DOI: 10.3390/polym11030508
|View full text |Cite
|
Sign up to set email alerts
|

Transcrystallization of Isotactic Polypropylene/Bacterial Cellulose Hamburger Composite

Abstract: Isotactic polypropylene (iPP) is a commonly used thermoplastic polymer with many excellent properties. But high brittleness, especially at low temperatures, limits the use of iPP. The presence of transcrystallization of iPP makes it possible for fiber-reinforced iPP composites with higher strength. Bacterial cellulose (BC) is a kind of cellulose with great potential to be used as a new filler to reinforce iPP due to its high crystallinity, biodegradability and efficient mechanical properties. In this study, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…The findings of the textural analysis carried out in this work are also useful in the case that BC will be used for other food or non-food purposes (e.g., fabrication of BC-based biocomposites for antibacterial films [26], thermoplastic polymers, and other materials [27]).…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the textural analysis carried out in this work are also useful in the case that BC will be used for other food or non-food purposes (e.g., fabrication of BC-based biocomposites for antibacterial films [26], thermoplastic polymers, and other materials [27]).…”
Section: Discussionmentioning
confidence: 99%
“…They registered the existence of PP transcrystallization throughout the BC fibers. 49 Ramos et al . registered transcrystallization in their work on recycled high-density polyethylene-gypsum composites.…”
Section: Resultsmentioning
confidence: 99%
“…They registered the existence of PP transcrystallization throughout the BC fibers. 49 Ramos et al registered transcrystallization in their work on recycled highdensity polyethylene-gypsum composites. 50 Mendes and Cestari reported this occurrence on composites of high density polyethylene filled with cellulosic fibers composites.…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%
“…For better compatibilisation, maleic anhydride grafted polypropylene (MAPP) was used. The authors reported that BC fibre provided transcrystallization of iPP, improving the mechanical properties with the additional contribution of MAPP as an interfacial agent [38]. In situ generation of biodegradable copolyester nanocomposites filled with 5, 10 and 20 wt.% of cellulose nanofibers (CNFs) was experienced by Hosseinnezhad.…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%